Pengaruh Metode Pengeringan Terhadap Kerusakan Karoten Mi Ubikayu Yang Diperkaya Tepung Labu Kuning (Effect Of Drying Method On Carotene Deterioration Of Cassava Noodle Enriched By Pumpkin Flour) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
Pumpkin flour has high 8-carotene, therefore, can be added to the noodle to alleviate vitamin A deficiency. Deterioration of 8-carotene may take place during drying, proper control of the process to minimize the deterioration is necessary. The objective of the research was to study the fl-carotene deterioration during drying process of the noodle and the phvsico-chemical properties of the cassava noodle that was enriched by pumpkin flour. The enrichment of the cassava flour was made by adding pumpkin flour in various proportions 0, 5,10 and 15 %. Noodle was sun dried for 8 hours, in a cabinet dryer at 60°C for 3 hours and in a two step cabinet driyer 60°C for 2 hours followed by drying at 55°C for 2 hours. The result showed that sun drying cause the greatest deteroriation of fl-carotene (46,24%). However, enrichment of pumpkin flour can improved the color, protein and fl-carotene content of the noodle.